BIM : interoperability issues between BIM authoring software and structural analysis software (RC) - Low, Khai Jer (Nanyang Technological University, 2021)
This is an era of digitalisation, software usage is ubiquitous across all industry, including the Built Environment industry, spanning from concept development, design, construction, operations till demolition of the building. BIM authoring software is a key pillar in improving the productivity and transforming the Built Environment. However, new issues arise when different software are adopted by the construction industry professionals with their daily works. One of the most significant issues that hindered the professionals and the construction industry from realising the full potential of BIM is the software's interoperability issue. This final year project pinpointed a gap in the current industry and focused on bridging it. This report scrutinised the most fundamentals issue in the software interoperability between the BIM authoring and Structural Analysis software, focusing on the aspects of transferring analysis results between the models in these software. During the solution development, Dynamo and Excel were used as intermediaries, where the deflection curves and the most critical member's utilisation ratio in the design groups were successfully exported from structural analysis software to BIM software. The potential practical applications of this project were also described. Lastly, future works were recommended for improvement.